Aspecte de drept comparat privind reglementarea juridică a clauzei de neconcurenţă în contractele de muncă - Mihailov, Tatiana (CEP USM, 2024)
Although the express regulation of the non-competition clause is a relatively recent one, it is certain that such a specific clause was found in individual employment contracts concluded between employees and employers until 2022. At the same time, as the conditions for the validity of such a clause were not expressly predetermined, most often employers were committing abuses and interpreting it as their exclusive right, without the need for them to comply with any correlative obligations, such as for example the payment of an allowance in favor of the employee or the geographical and temporary limitation of the action of such a clause. In these cases, of course, the insertion of such a non-competition clause in individual employment contracts with the exclusive limitation of the right to carry out any activity by the former employee was in obvious contradiction with the constitutional right to work, established by art. 43 of the Constitution of the Republic of Moldova.
COMPARATIVE LAW ASPECTS REGARDING THE LEGAL REGULATION OF THE NON-COMPETION CLAUSE IN EMPLOYEMENT CONTRACTS
Keywords: non-competition clause; non-competition allowance; freedom of work; employee angajator; clauza de neconcurență; indemnizație de neconcurență; libertatea muncii; salariat